Monitoring Curah Hujan dan Kelengasan Tanah Lahan Pertanian Menggunakan Sensor Berbasis Internet of Things (IoT) sebagai Dasar Pertanian Presisi - Saydi, Royhan (Jurnal Ilmiah Teknologi Pertanian Agrotechno, 2021)
the spatial and temporal variability aspects by utilizing technology to monitor the location. Monitoring is carried out to obtain data and information on certain land conditions, with the aim of minimizing the risk of crop failure and increasing crop productivity. The development of control systems and sensors affects the development of the monitoring system. Information about the right temperature, humidity and light intensity can be used as data by farmers in increasing the process of growth and development of plant cultivation. Development of a monitoring system on agricultural land, especially in soil and environmental conditions, is the basis for assessing land characteristics. The design of the tool uses a microcontroller and supporting sensors. This unit of monitoring, control and sensor systems forms the basis for the application of precision agriculture. The application of automatic weather sensor (automatic wheater station) can help in realtime weather data retrieval in a short time. The results of the trial application of the sensor show that data is recorded offline once every 1 minute and online once every minute. Information data becomes material for farmers in making decisions about providing water and fertilizers. This monitoring system tool supports the Internet of Things (IoT) in sending weather data so that the results of sensor measurement data can be observed on the thingspeak.com website platform. Keyword: Agriculture, IoT, Precision Agriculture